Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 114681 by Dwaipayan Shikari last updated on 20/Sep/20

Prove that ∫_0 ^∞ (x^n /(e^x −1))dx=n!ζ(n+1)

Provethat0xnex1dx=n!ζ(n+1)

Answered by mnjuly1970 last updated on 20/Sep/20

          proof::             Ω=  ∫_0 ^( ∞) (x^n /(e^x −1))dx =∫_0 ^( ∞) ((x^n e^(−x) )/(1−e^(−x) ))dx               = ∫_0 ^( ∞) Σ_(m=1) ^∞ x^n e^(−mx) dx=Σ_(m=1) ^∞ ∫_0 ^( ∞) x^n e^(−mx) dx           =^(⟨mx = t ⟩)  Σ_(m=1) ^∞ ∫_0 ^( ∞) ((t^((n+1)−1)  e^(−t) )/m^(n+1) )dt =Σ_(m=1) ^∞ ((Γ(n+1))/m^(n+1) )              Ω=Γ(n+1).Σ_(m=1) ^∞  (1/m^(n+1) )= n! ζ(n+1)                ✓ note (1) ::  Γ(n+1)=nΓ(n)=n!               ✓  note (2) ::  ζ(s) =Σ_(n=1) ^∞ (1/n^s )                    ...m.n. july 1970#...

proof::Ω=0xnex1dx=0xnex1exdx=0m=1xnemxdx=m=10xnemxdx=mx=tm=10t(n+1)1etmn+1dt=m=1Γ(n+1)mn+1Ω=Γ(n+1).m=11mn+1=n!ζ(n+1)note(1)::Γ(n+1)=nΓ(n)=n!note(2)::ζ(s)=n=11nsYou can't use 'macro parameter character #' in math mode

Commented by Dwaipayan Shikari last updated on 20/Sep/20

Great sir!

Greatsir!

Commented by mnjuly1970 last updated on 20/Sep/20

p.b.h.y you are welcom

p.b.h.yyouarewelcom

Commented by Tawa11 last updated on 06/Sep/21

great sir

greatsir

Answered by mathdave last updated on 20/Sep/20

solution   let I=∫_0 ^∞ (x^n /(e^x −1))dx=∫_0 ^∞ ((e^(−x) x^n )/(1−e^(−x) ))dx  series of  (1/(1−e^(−x) ))=Σ_(k=0) ^∞ e^(−kx) =Σ_(k=1) ^∞ e^(−x(k−1)) =Σ_(k=1) ^∞ e^(−kx+x)   I=Σ_(k=1) ^∞ ∫_0 ^∞ e^(−x) x^n e^(−kx+x) dx=Σ_(k=1) ^∞ ∫_0 ^∞ x^n e^(−kx)   let y=kx,dx=(dy/k)  I=Σ_(k=1) ^∞ ∫_0 ^∞ e^(−y) ((y/k))^n (dy/k)=Σ_(k=1) ^∞ (1/k^(n+1) )∫_0 ^∞ e^(−y) y^n dy  I=Σ_(k=1) ^∞ (1/k^(n+1) )∫_0 ^∞ y^((n+1)−1) e^(−y) dy  I=ζ(n+1)Γ(n+1)     but Γ(n+1)=n!  ∵∫_0 ^∞ (x^n /(e^x −1))=n!ζ(n+1)      Q.E.D  by mathdave

solutionletI=0xnex1dx=0exxn1exdxseriesof11ex=k=0ekx=k=1ex(k1)=k=1ekx+xI=k=10exxnekx+xdx=k=10xnekxlety=kx,dx=dykI=k=10ey(yk)ndyk=k=11kn+10eyyndyI=k=11kn+10y(n+1)1eydyI=ζ(n+1)Γ(n+1)butΓ(n+1)=n!0xnex1=n!ζ(n+1)Q.E.Dbymathdave

Answered by Aziztisffola last updated on 20/Sep/20

∫_0 ^∞ (x^n /(e^x −1))dx=∫_0 ^∞ (x^n /e^x ) (1/(1−e^(−x) ))dx  =∫_0 ^∞  (x^n /e^x ) Σ_(k=0) ^∞ e^(−kx)  dx  =Σ_(k=0) ^∞  ∫_0 ^( ∞) x^n e^(−kx−x) dx  =Σ_(k=0) ^∞  ∫_0 ^( ∞) x^n e^(−(k+1)x) dx  let t=(k+1)x ⇒dt=(k+1)dx   ⇒ Σ_(k=0) ^∞ ∫_0 ^( ∞) ((t/(k+1)))^n e^(−t) (dt/(k+1))  =Σ_(k=0) ^∞ ∫_0 ^( ∞) (t^n /((k+1)^(n+1) )) e^(−t) dt  = Σ_(k=0) ^∞ (1/((k+1)^(n+1) ))∫_0 ^( ∞) t^n e^(−t) dt  =∫_0 ^( ∞) t^n e^(−t) dtΣ_(k=0) ^∞ (1/((k+1)^(n+1) ))  =∫_0 ^( ∞) t^((n+1)−1) e^(−t) dtΣ_(k=1) ^∞ (1/((k)^(n+1) ))  =Γ(n+1)ζ(n+1)  =n!ζ(n+1)

0xnex1dx=0xnex11exdx=0xnexk=0ekxdx=k=00xnekxxdx=k=00xne(k+1)xdxlett=(k+1)xdt=(k+1)dxk=00(tk+1)netdtk+1=k=00tn(k+1)n+1etdt=k=01(k+1)n+10tnetdt=0tnetdtk=01(k+1)n+1=0t(n+1)1etdtk=11(k)n+1=Γ(n+1)ζ(n+1)=n!ζ(n+1)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com